2015
DOI: 10.1155/2015/341740
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase‐9 Production following Cardiopulmonary Bypass Was Not Associated with Pulmonary Dysfunction after Cardiac Surgery

Abstract: Background. Cardiopulmonary bypass (CPB) causes release of matrix metalloproteinase- (MMP-) 9, contributing to pulmonary infiltration and dysfunction. The aims were to investigate MMP-9 production and associated perioperative variables and oxygenation following CPB. Methods. Thirty patients undergoing elective cardiac surgery were included. Arterial blood was sampled at 6 sequential points (before anesthesia induction, before CPB and at 2, 4, 6, and 24 h after beginning CPB) for plasma MMP-9 concentrations by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Various research groups described increased activities of MMP-9 in patients after surgery [50][51][52]. However, the increase of MMP-9 activities in our patients was significantly lower after four weeks of intervention with Robuvit compared to the placebo (p = 0.006).…”
Section: Discussioncontrasting
confidence: 64%
“…Various research groups described increased activities of MMP-9 in patients after surgery [50][51][52]. However, the increase of MMP-9 activities in our patients was significantly lower after four weeks of intervention with Robuvit compared to the placebo (p = 0.006).…”
Section: Discussioncontrasting
confidence: 64%
“…Indeed, it was detected that after CPB plasma MMP-9 levels were significantly elevated reaching control levels after about 24 h. As a consequence leucocyte counts were also increased. However, as described in the patient trial of Lin et al ( 2015 ) this was not associated with bypass time or pulmonary dysfunction. In contrast, another patient trial showed that elevated MMP-8 and MMP-9 levels are associated with impaired oxygenation and pulmonary dysfunction after CPB (Beer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 56%
“…A total of 20 relevant publications were retrieved for further assessment. Fifteen trials that enrolled a total of 431 participants met the inclusion criteria and were included in the systematic review [6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23]. Two review authors (F.J., G.F.S.)…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies included, 5 were prospective RCTs (n = 211) [6,7,16,18,19], and 1 was a retrospective observational study [23], whereas the remaining 9 were prospective observational NRCTs [11][12][13][14][15]17,[20][21][22]. All studies included patients submitted to cardiac surgery with CPB, but some better defined their population: seven studies enrolled patients undergoing CABG with CPB (n = 213) [7,[11][12][13][14]16,21], one study included patients submitted to off-pump or on-pump CABG [15], one enrolled patients submitted to pericardiectomy with CPB [23], and one included patients undergoing to CABG or valve replacement with CPB [6].…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation